2016
DOI: 10.1111/ejss.12380
|View full text |Cite
|
Sign up to set email alerts
|

Changes in flow and transport patterns in fen peat following soil degradation

Abstract: The preferential movement of water and transport of substances play an important role in soil, but they are not yet fully understood, especially in degraded peat soil. In this study, we aimed to deduce changes in flow and transport patterns with titanium dioxide (TiO2) as a dye tracer during the course of soil degradation resulting from peat drainage. The dye tracer experiments were carried out on columns of eight types of differently degraded peat soil from three sites taken in both vertical and horizontal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 38 publications
8
65
0
Order By: Relevance
“…With the beginning of decomposition of plant residues and soil compaction, a clear reduction of macroporosity occurred. With the further mineralization of organic matter, macroporosity remained almost constant because of the generation of secondary macropore space (e.g., root and worm channels; Liu & Lennartz, ; Liu et al, ). This sequence supports results for a single site investigated by Schwärzel et al ().…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…With the beginning of decomposition of plant residues and soil compaction, a clear reduction of macroporosity occurred. With the further mineralization of organic matter, macroporosity remained almost constant because of the generation of secondary macropore space (e.g., root and worm channels; Liu & Lennartz, ; Liu et al, ). This sequence supports results for a single site investigated by Schwärzel et al ().…”
Section: Discussionsupporting
confidence: 93%
“…Generally, peatland drainage decreases total porosity, accompanied by a shift in pore size distribution (Rezanezhad et al, ; Wallor et al, ). Macropores are an important feature of pore structure in peat soils (Baird, ; Holden, ) and have a large effect on hydraulic properties (Baird, ; Liu, Janssen, & Lennartz, ). During peat decomposition and degradation processes, macroporosity decreases and microporosity increases (Rezanezhad et al, ; Silins & Rothwell, ), although a higher macroporosity could be observed in strongly decomposed peat than in less decomposed peat (Schindler, Behrendt, & Müller, ; Wallor et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally to the K s tests, a salt tracer test combined with a determination of the DOC content was carried out for three soil columns of Peat F1 (relating to Hypothesis 3). They were placed in a flow‐through device connected to a peristaltic pump (an illustration of the set‐up can be found in Liu, Janssen, and Lennartz, ) and were saturated for 1 day with water with an EC of 0.7 mS cm −1 . Subsequently, two pore volumes with the same EC were pumped through (0.7 ml min −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Cl − MIM 9.81 × 10 −2 6.66 × 10 −2 fixed to 1 1.00 100 a 0.9 0.032 −406 (91 %) (19 %) (1510 %) (N/E) (N/E) CDE 9.79 × 10 −2 6.66 × 10 −2 fixed to 1 n/a n/a n/a 0.032 −408 (1 %) (7 %) Na + CDE fixed fixed 2.65 n/a n/a n/a 0.145 −229 (3 %) OSA fixed fixed 3.07 n/a 0.5 b 1.12 × 10 −3 0.024 −443 in laboratory studies that breakthrough experiments on peat need to be described by the MIM (Hoag and Price, 1997;Rezanezhad et al, 2012;Liu et al, 2016;Rezanezhad et al, 2017;Thiemeyer et al, 2017). Additionally, this finding is reflected in the fact that a multimodal retention curve was not observable, which would have been indicative for a twodomain flow of solute transport.…”
Section: Solute Transport Model Selectionmentioning
confidence: 99%